Insights on Morphology and Thermal Stability of Hollow Pt Nanospheres by In Situ Environmental TEM - Josephine Rezkallah; Xavier Sauvage; Bernhard Witulski; Simona Moldovan (Molecules)
The fields of catalysis and energy storage nowadays quote the use of nanomaterials with well-defined size, morphology, chemical composition, and thermal stability in the high-temperature range and under harsh conditions of reactions. We present herein an approach based on in situ environmental scanning transmission electron microscopy (STEM), combined with analytical STEM and electron tomography (ET), for the evaluation of the thermal stability of hollow Pt nanospheres under vacuum and high-pressure hydrogen environments. Spherical Pt hollow nanospheres (HNSs) with an average diameter of 15 and 34 nm were synthesized by a galvanic replacement-based procedure using either steep or continuous addition of Pt salts during synthesis. The as-synthesized HNSs exhibit complex 3D structures with shells of a few nm constituted by small Pt nanoparticles and marked by the presence of open channels. The thermal stability of Pt-based HNSs under TEM vacuum and 1 bar of hydrogen flow is reported by considering microstructural changes, e.g., the build-up of a continuous shell and its evolution until HNSs collapse at elevated temperatures (>500 °C). Experimental findings are discussed considering fundamental phenomenological issues, i.e., NP faceting, NP diffusion, and subsequent NP sintering, with respect to the behavior of the systems investigated.